Developing a crosswalk between the RAND-12 and the health utilities index for multiple sclerosis. (August 2020) - Marrie, Ruth Ann; Dufault, Brenden; Tyry, Tuula; Cutter, Gary R; Fox, Robert J; Salter, Amber
Background: Researchers studying health-related quality of life (HRQOL) in multiple sclerosis (MS) can choose from many instruments, but findings from studies which use different instruments cannot be easily combined. We aimed to develop a crosswalk that associates scores from the RAND-12 to scores on the Health Utilities Index—Mark III (HUI3) in persons with MS. Methods: In 2018, participants in the North American Research Committee on Multiple Sclerosis (NARCOMS) registry completed the RAND-12 and the HUI3 to assess HRQOL. We used item-response theory (IRT) and equipercentile linking approaches to develop a crosswalk between instruments. We compared predicted scores for the HUI3 from each crosswalk to observed scores using Pearson correlations, intraclass correlation coefficients (ICCs), and Bland–Altman plots. Results: Of 11, 389 invited participants, 7129 (62.6%) responded. Predicted and observed values of the HUI3 from the IRT-linking method were moderately correlated (Pearson r  = 0.76) with good concordance (ICC = 0.72). However, the Bland–Altman plots suggested biased prediction. Predicted and observed values from the equipercentile linking method were also moderately correlated (Pearson r  = 0.78, ICC = 0.78). The Bland–Altman plots suggested no bias. Conclusion: We developed a crosswalk between the RAND-12 and the HUI3 in the MS population which will facilitate data harmonization efforts.